THE JUNIOR LEARNER’S MORAL – ETHICAL EVALUATION ACTION BUILDUP - Vitkovskaya, Irina; Khrabrova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The moral – ethical evaluation action in the federal state educational standard of primary education is regarded as a universal educational activity, the formation of which provides the optimal development of junior learners, the possibility of a successful continuation of education, adaptation in society. The article describes one of the approaches to the formation of the action based on the content of the subject "Fundamentals of Orthodox Culture"